FEATURES OF INDUSTRIAL ZONE RENOVATION AND ITS ADAPTATION TO THE MODERN URBAN ENVIRONMENT - Ivanenko, Bohdan (Theory and practice of design, 2023)
In the article, the main aspects of industrial zone renovation and the identified impractical use of these areas are discussed. The understanding of the role and potential of renovating industrial zones in the context of modern urban development is examined and described. By analyzing the dynamics of economic, environmental, and socio-cultural changes accompanying urban development, the article emphasizes the importance of adapting industrial areas for achieving sustainable development. The research underscores the possibilities of adapting these objects to contemporary needs and transforming them into functional spaces that promote sustainable development and improve the quality of urban life. Purpose. The primary goal is to highlight the potential for adapting industrial areas to contemporary needs and their transformation into functional spaces that contribute to sustainable development and improve the quality of urban life. The study also examines methods of improving industrial-purpose territories while considering the preservation of architectural value and the importance of preserving historical heritage. Methodology. Theoretical research methods, analysis of international experience in industrial zone renovation, and the application of graph-analytical methods are used. Results. The identification of key directions and methods for renovating industrial areas. Scientific novelty. The article presents a perspective that the renovation of industrial areas can impact contemporary urban planning and create a new economic and tourist structure for the use of these territories, promoting the improvement of urban infrastructure. Practical relevance. The article analyzes methods of improving industrial-purpose territories while considering the preservation of architectural value. One of the key aspects addressed in the article is the preservation of architectural heritage in industrial areas. Often, these zones have historical value, and their reconstruction or renovation can contribute to both preserving this heritage and creating unique spaces for contemporary use. The research examines the formation of objects in accordance with modern urban planning requirements, as well as the economic aspects of industrial zone renovation. The transformation of these territories can create new opportunities for businesses and investments, which will contribute to urban development and the creation of new jobs. The study explores possible strategies for urban development, including public involvement and the formation of partnerships between municipal authorities and businesses. This article emphasizes the importance of considering various aspects that affect the renovation and adaptation of industrial zones in the modern urban environment. In particular, the article emphasizes the importance of considering ecological aspects in renovation projects. Ensuring the sustainability of the urban environment and reducing the negative impact on the surrounding environment are essential goals in the transformation of industrial zones. Furthermore, the article conducts a comparative analysis of domestic and international experience in renovating industrial areas and highlights factors that directly influence the successful implementation of renovation and adaptation projects in the modern urban environment.